A course in modern analysis and its applications - Cohen, Graeme Laurence (Australian Mathematical Society lecture series, 2003)
Designed for one-semester courses for senior undergraduates, this book approaches topics initially through convergence of sequences in metric space. However, the alternative topological approach is also described. Applications are included from differential and integral equations, systems of linear algebraic equations, approximation theory, numerical analysis and quantum mechanics.